2021
DOI: 10.1088/1367-2630/ac08b4
|View full text |Cite
|
Sign up to set email alerts
|

Unified treatment of recoil and Doppler broadening in molecular high-energy photoemission

Abstract: Doppler and recoil effects are an integral part of the photoemission process at the high kinetic energies reached in hard x-ray photo-electron spectroscopy (HAXPES) and have a major effect on the observed lineshape, resulting in broadening, energy losses and discrete excitations. These effects can be modeled with a high degree of detail for small systems like diatomic molecules, for larger systems such treatment is often superfluous as the fine spectral features are not observable. We present a united descript… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Development of synchrotron-based high-resolution electron spectroscopy, especially in the HAXPES regime, has allowed to directly investigate the recoil-induced effects in the molecular core-level photoemission of single gas-phase molecules and to model them at various levels of precision. 14,25,29,30 These and other experimental studies have uniformly confirmed the validity of the fundamental assumptions in the recoil models, which can be summarized as follows:…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Development of synchrotron-based high-resolution electron spectroscopy, especially in the HAXPES regime, has allowed to directly investigate the recoil-induced effects in the molecular core-level photoemission of single gas-phase molecules and to model them at various levels of precision. 14,25,29,30 These and other experimental studies have uniformly confirmed the validity of the fundamental assumptions in the recoil models, which can be summarized as follows:…”
Section: Introductionsupporting
confidence: 57%
“…Knowing the coefficients f n , the Poisson distributions of recoil-induced vibrational excitations in each vibrational oscillator n at T = 0 K can be obtained. 25 They have the mean (average recoil energy), variance and skewness as…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In near future, we also expect 2D-maps with significantly higher experimental resolution to provide more detailed information, since new high-resolution monochromators in the HAXPES regime are now available, providing a photon energy resolutions of E /Δ E of almost 50.000 at 7 keV. 46 2D-Maps measured with such high experimental resolution will reveal in particular in the resonant Auger region much finer details and will provide a benchmark for theoretical descriptions.…”
Section: Discussionmentioning
confidence: 96%
“…5,9 However, in the case of molecular fragments possessing several vibrational degrees of freedom, there are more ways to dissipate the internal energy as well as to excite recoil-induced vibrations and rotations. 20 Dispersion of the E KER with the electron energy, extracted from the experimental data for the NH 2 + –H dissociation channel, shows that about 43% of the internal energy remaining in the system after emission of the resonant Auger electron is transferred to vibrations, while recoil-induced rovibronic excitations are weak owing to the relatively high mass ratio of the co-fragments ( m NH 2 / m H = 16 : 1).…”
Section: Introductionmentioning
confidence: 99%